A new load transfer index () with considering six degrees of freedom and its application in structural design and analysis. Issue 4 (4th July 2018) - Wang, Qingguo; Telichev, Igor; Wu, Christine Q.
ABSTRACT: Load paths analysis is important in design process of load bearing structures. U * index was introduced as the indicator of load paths based on finite element analysis. However, the U * index was only formulated based on three translational degrees of freedom (DOFs) without considering the rotational DOFs. Hence, the U * index cannot be used together with plate and shell theories, which are very important in engineering computations of thin-walled structures. A coupling issue in finite element analysis is that shell elements which are governed by plate and shell theories are invalid for U * calculations. This paper proposed a new load transfer index ( ) with considering both translational and rotational DOFs (i.e. six DOFs). To demonstrate the effectiveness of the new index in structural design and analysis, a case study was performed to a complex thin-walled structure. The stiffness to mass ratio of the sample structure is raised by 18.3% based on the load transfer analysis using the new index.